THE EFFECT OF SUPPLEMENTATION EXTRACT OIL HABATUSSAUDA (Nigella sativa) ON MALE MICE REPRODUCTION (Mus musculus): PENGARUH SUPLEMENTASI EKSTRAK MINYAK HABATUSSAUDA (Nigella sativa) TERHADAP REPRODUKSI MENCIT JANTAN (Mus musculus) (Jurnal Peternakan Nusantara, 2023)
The increased of free radicals and DNA damage in spermatozoa may effected to male fertility, so we need antioxidant component to prevent the damage. Habbatussauda (Nigella sativa) is a herbal indicated to improved spermatogenesis function. This study was aimed to get information about Habbatussauda suplementation effect on mice testicle function. Thirty six male mice of 4 week aged were divided into four group, each group consists of nine mice. Group I was negative control (received aquadest), group II (received 0.1 ml Habbatussauda oil extract), group III (received 0.2 ml Habbatussauda oil extract), and group IV (received 0.3 ml mixed of Habbatussauda oil extract and honey). This treatment during for two month, and the mice were euthanized and necropsied for collection testis organ as sample. The sample was processed to prepare histology slides with Hematoxylin-Eosin stain. The parameters observed include to count on and differenciate of the spermatogenic cells, Sertoli cell, and Leydig cell using software Image J®. Qualitative data were analyzed with SPSS® software with ANOVA test and followed by Duncan test. The result showed that Habbatussauda caused increasing of spermatogenic cells, Sertoli cell, and Leydig cell on group II, III, and IV which were significant (P<0.05) with the negative control group.